PENGARUH MODEL EXPERIENTIAL LEARNING BERBANTUAN MEDIA PEMBELAJARAN YOUTUBE TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 3 BALIKPAPAN - Fitri, Andi; Sudarman, Sudarman; Abu, Ilham (Educational Studies: Conference Series, 2023)
This research aims to determine the effect of the experiential learning model assisted by YouTube learning media on the learning outcomes of class X students at SMA Negeri 3 Balikpapan. This research uses a quasi-experimental method with a nonequivalent control group design. The subjects of this research were students in class X-3, totaling 36 students, as the experimental class and X-6, totaling 36 students, as the control class. The data collection technique used in this research is a test, namely pretest and posttest, then supported by other data in the form of documentation with data analysis using the sample t-test. The research results show that the sig. (2-tailed) t-test for Equality of means is 0.001 so that the significance value is 0.001 < 0.05, which means H0 is rejected and Ha is accepted. So, it can be concluded that there is a significant influence of the experiential learning learning model assisted by YouTube learning media on the economic learning outcomes of class X SMA Negeri 3 Balikpapan students.